Pengaruh Celebrity Endorser dan Kualitas Produk Terhadap Keputusan Pembelian Pada MS Glow Pekanbaru Cabang Delima (Ms Glow Stockist Grosir) - Lilis Juliyanti; Endang Sutrisna (eCo-Buss, 2025)
This study investigates the effects of celebrity endorsers and product quality on consumer purchasing decisions at MS Glow Delima Branch in Pekanbaru. It is hypothesized that utilizing celebrities for promotions can enhance brand appeal and motivate consumer purchasing behaviors. Moreover, the quality of the product is also crucial in building consumer trust and loyalty. A quantitative research approach was employed, gathering data through surveys administered to 100 consumers at the MS Glow Pomegranate Branch. The data was analyzed using multiple linear regression techniques. The results reveal that celebrity endorsers significantly and positively influence purchasing decisions, underscoring the effectiveness of MS Glow's choice in celebrity partnerships in swaying consumer behavior. Similarly, high product quality also positively impacts purchasing decisions, highlighting consumer preference for high-quality goods. Collectively, these factors are pivotal in influencing purchasing choices. The study suggests that MS Glow should continue leveraging celebrity endorsements and uphold high product standards to sustain consumer loyalty.